In-Silico Methods for Investigating the Effect of Single Nucleotide Polymorphisms on the Structure and Function of Proteins - Asiedu, E. (International Journal of Scientific Research in Biological Sciences, 2019)
Single nucleotide polymorphisms (SNPs) are associated with diseases and drug response variabilities in humans. Elucidating the damaging and disease-associated SNPs using wet-laboratory approaches can be challenging and resource-demanding due to the large number of SNPs in the human genome. Due to the growth in the field of computational biology and bioinformatics, algorithms have been developed to help screen and filter out the most deleterious SNPs that are worth considering for wet-laboratory studies. This article reviews the existing in-silico based methods used to predict and characterize the effects of SNPs on protein structure and function. This cutting-edge approach will facilitate the search for novel therapeutics, help understand the etiology of diseases and fast-track the personalized medicine agenda.